Do near-bedtime usage of smartphones and problematic internet usage really impact sleep? A study based on objectively recorded usage data - Aftab Alam (5158601) (2023)
Objective Existing research reporting an association between smartphone usage and sleep quality has often utilised subjective self-reported smartphone usage and sleep data. This paper aims to study the associations of objectively collected smartphone near-bedtime usage and problematic internet usage (PIU) with parameters of sleep quality. Methods The dataset had 269 (55% Female, 55.13% Adults) participants. From the acquired usage data, the daily averages of sleep duration, sleep distraction, and smartphone usage two hours before sleep were extracted. Results The multivariate linear regression showed that the increase in PIU (β = −0.231, p < 0.001) and smartphone usage two hours before sleep (β = −0.246, p < 0.001) led to decrease in sleep duration. Regarding sleep distraction, multivariate linear regression analysis revealed that two hours before sleep was a significant and positive predictor of sleep distraction (β = 0.197, p = 0.003), whereas PIU was not significant. Conclusion Longer duration of smartphone usage before sleep and higher PIU were associated with reduced sleep duration and continuity. PIU predicted the possibility of getting distracted while usage before sleep predicted the distraction duration. Our results confirm and elaborate on concerns about technology overuse near bedtime and call for specialised interventions to help healthier technology design and usage styles. Other Information Published in: Behaviour & Information Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/0144929x.2023.2279648